44 Wirral's Teletriage Service. (6th February 2020) - Whittle, E; James, E; Smith, A; Highton, M; Shaikh, S; Stone, B; Thompson, J; Orr, T; Hogan, I; Stokes, S; Langton, J; Chu, C; et al.
Abstract: Introduction: The Wirral Teletriage Service provides non-urgent clinical support to Wirral Care Homes in order to help avoid unnecessary hospital admissions for their residents. It also aims to provide quicker access to clinical assessment than via NHS 111 and to provide this care in the patient's residence wherever possible. Methods: Care homes call the Teletriage service when they have concerns about the health of one of their residents. The Teletriage nurse undertakes a clinical assessment of the resident remotely via Skype. Care Homes have been provided with a secure NHS email address to facilitate secure sharing of data. They have also been provided with iPads and training for their staff. After being assessed by Teletriage, residents are signposted to the most appropriate care pathway for their needs. Results: 76 Care Homes have signed up to the service. On average, the Teletriage Service receives 300-400 calls a month. In an 18 month period, the number of calls to NHS 111 have reduced by 76%. Out of all the calls to Teletriage, 22% of patients were managed by the Teletriage team with no onward referral, 57% were managed via community services e.g GPs, Community Geriatricians, and 10% were referred to the ambulance service. Emergency Health Care Plans (EHCPs), Preferred Priorities of Care and EOL (End of Life) wishes are taken into account. Conclusions: The Teletriage project has reduced the number of phone calls to NHS 111 and the ambulance service, and subsequently has reduced the number of patients conveyed to hospital by 12%. The Teletriage nurses work very closely with various community services as well as GPs, NWAS and Community Geriatricians. The ongoing training and education provided to the Care Home Staff means that overall there has been good engagement with the project from the majority of the Wirral Care Homes.